Physical separation for upgradation of valuable minerals: a study on sands of the Someswari river (Bangladesh Journal of Scientific and Industrial Research, 2015)
The study is carried out to develop a physical separation method for upgradation of valuable minerals from sands of the Someswari River. Understanding the morphology and mineralogy of the heavy minerals may allow development of processing methods that produce the higher grade products. For this purpose, grain size analysis, microscopic, spectroscopic study and feasibility of physical separation by shaking table, electrostatic plate separator and induced roll magnetic separator have been done. Considering the huge quantity of sandy materials of the studied river sands and separation of heavy minerals magnetite, ilmenite and garnet from the bulk sands and further treatment of the light mineral quartz to remove iron coating could be use as glass-sands; either the light mineral quartz or heavy minerals will be the main product. From the overall study by physical separation method, the Someswari River is identified as potential resources for mineral processing.Bangladesh J. Sci. Ind. Res. 50(1), 53-58, 2015